Relationship of dryland power measures and swimming performance - Johnson, M. D. (Journal of Australian Strength and Conditioning, 2020)
Strength training for swimmers has been shown to benefit swim performance, with 6-week interventions shown to decrease swim time by 1.2%-4%. Previous research has found that counter movement jump peak velocity and peak power correlate strongly with swim starts (r = 0.78). However, the evidence for which dryland power measures relate to the swim phase of a race has yet to be comprehensively compiled. The purpose of this review is to compile the research and isolate the findings on power measures associated with swimming power outside of starts and turns. This narrows the focus towards upper body dryland power measures, and which are most critical and closely related to swimming performance. Literature was gathered utilising a specific inclusion criterion. The identified keywords for inclusion were; 1) swimming, 2) dryland, 3) power, 4) performance, 5) strength, 6) force. The review found that velocity and power measures were superior to measures of force. 1RM bench press was found to have a moderate correlation with swimming power (r=0.477) and the maximum velocity bench press was found to have a stronger relationship (r=0.624). The strongest correlation for dryland force measurement to swim performance was found to be a 1RM latissimus pulldown (r=0.643). The mean velocity of a pull-up was correlated against 50m freestyle time with a strong correlation found (r=0.88). It was found that measures of velocity and power are crucial for relating dryland performance to in-water performance. The application of velocity and power to vertical pulling exercises, chin-ups, pull-ups and latissimus pulldown, appears to be the best dryland indicator of swimming performance.